PERBANDINGAN PENERAPAN METODE WAKTU BAKU DENGAN PENDEKATAN TIME STOP PADA SISTEM SWIFT SAP ENTERPRISES PADA WORKSHOP PERAWATAN PASSENGER SEAT BOEING 747-400 DI PT. GMF AEROASIA TBK - Tina Hernawati Suryatman; Mukhammad Yusuf Hakim; Hartono Hartono (Universitas Muhammadiyah Tangerang, 2019)
PT. GMF Aero Asia is Maintenance, Repair and Overhaul (MRO). The Cabin Maintenance Unit (Furnishing Service and Uphostery) is responsible for work related to the interior area of the aircraft. Included in the component is the Passenger Seat. Cabin Maintenance Office at GMF in performing maintenance services which have several different types of problems, namely in terms of billing to customers there are two indicators, including material, manpower and man hours. The company has an old system, the SAP 2010 series, where all work processes cannot be covered so it requires several additional applications. In response to this, the company provides a new system that can make all data analysis in one application. The system has been used by several airlines throughout the world. Namely the latest SAP with the name SWIFT SAP Enterprise, but the new system is not running without problems. Because basically the use of SWIFT SAP Enterprises which refers to the applicable maintenance manual is very inflexible as well as a lot of actual time in the field that is not counted in billing. In this case, improvements will be made by comparing the application of one of the principles of Time Motion Study to the system used by PT. GMF Aero Asia recently. All aspects will be examined so that the best results can be known. The questionnaire will also be distributed before and after the application of the method. So that it can be seen from all aspects related not only production but all supporting staff who are in the Maintenance area. The research will also solve the problem of both the general aspects of the unit's production and finance as a whole for one year. So that it can be known with certainty the advantages and disadvantages that occur during the treatment process. After all the analysis was done, it was found that there were some deficiencies that occurred in the SAP Enterprises system, where a lot of profit was lost from the maintenance process that occurred. So there are several alternatives that can be taken by Cabin Base Maintenance shop units. Alternatives taken include making rearranging work hours based on actual time with the draft that has been made. Arranging training schedules for employees regarding the Swift system in accordance with their work area. And counseling about financial issues related to the flow of work in the Workshop Seat Cabin maintenance area. Keywords: SWIFT SAP Enterprise, Passenger Seats, Time Movement Study, Stop Time, Normal Time, Cycle Time, Overtime, Calculator